Pengembangan Modul Interaktif Berbasis Multiple Intelligence dengan Autoplay pada Konsep Perubahan Materi Genetik di IKIP Budi Utomo Malang - Nisa, Khoirun; Setiawan, Deny (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Technology-based learning needs to be done immediately in order to carry out more interested in learning and fostering student motivation. Furthermore, learning should be done by each student characteristics. One of which is multiple intelligences based learning. Through the application of multiple intelligence assisted technology based learning, it is expected that the learning objectives will be more easily achieved by students. Interactive module based on multiple intelligences that has been validated was the product of this research and developmental experiment. This research was limited to the Changes of Genetic Material taught at the Genetics Course at IKIP Budi Utomo Malang. Research and development model was carried out by 4D model from Thiagarajan (1974). This research phase includes define, design, design, and disseminate stages. The research data is obtained from the module validation score, both from material experts, media experts, and practitioners (students). The data obtained were analyzed qualitatively and quantitatively. Based on the results of the validation of media experts, material experts and small-scale trials, it is known that the percentage results are above 85%, so the product is declared valid. Furthermore, it is necessary to test the classical scale to find out its effectiveness in learning.